Invited Guest Editorial: Quaint Memories of Puzzling Through Mysteries - James Colin Field (University of Calgary, 2016)
The incompleteness of meaning and the finitude of understanding suggest that the subject matters (die Sache) of understanding are mysteries rather than problems. Mysteries are not subject to the methodological solutions problems are. A problem denotes a difficulty demanding a solution. Mysteries however can only be understood more deeply. They are not to be explained away but are to be discerned as an ever-present limit to our understanding. They invoke an apprehension of a radical limitlessness (Davey, 2006, p. 29). I had the good fortune of supervising John’s thesis—a mysterious venture to be sure, because when we started, neither the path nor the destination were clear. In this editiorial I preface John's latest installment of his serialization of The Case of the Disappearing/Appearing Slow Learner: An Interpretive Mystery. Part Four: Quaint Notions of Justice.